Design of training center units - ابو شيخه, براء; غياضه, احمد (جامعة بوليتكنك فلسطين - مباني, 2015)
The project is consisting of three architectural components as separated units of a whole training center among them are a training hall, connected pair of underground water tanks , and club house. As for the training hall, it is a reinforced concrete structure with a height of 6 meters with a ceiling resting directly on an edge- distributed columns without any of them inside the central space, so that we can get fairly use of the whole existing central space. Dimensions of the hall are given to be: 40 m*80m with a total area of 3200 sqr.m. The pair of underground water tanks are being separated by a wall to have two-2800 cubic meters tank-capacity with 20m*20m 7m for each of them. The last of the center components is the club house, which consists of multi leveled –one floor , with a total area of 2000 sqr.m Lastly , at this semester , should the architectural and structural designs properly be accomplishedfor some of the units. The ACI-318-08 code will be used in the design operations, whereas the 2006-jordanian code of loads will be used for load calculations.
التصميم الانشائي لاجزاء من مركز تدريب
no of pages 130, 28828, مباني 3/2015, in the store
Keywords: التصاميم الانشائية; الابنية التعليمية